Linguistic Traces of Subjectivity and Dissent. A Discursive Analysis of Inclusive Language in Argentina - Tosi, Carolina (Frontiers in Sociology, 2021)
In Argentina, the so-called “inclusive language” aims at avoiding the bias for a particular sex or gender and objects to a grammatical binary system (feminine – masculine). Although in most Spanish-speaking countries, inclusive language has been limited to the realms of activism, gender studies and a certain type of public administration, in Argentina, its use has been extended to different social spheres, mostly urban. Considering such context, and employing the Dialogical Approach to Argumentation and Polyphony, this work seeks to address inclusive language resources as subjectivity and polyphony marks which evidence certain aspects of the discourse of patriarchy, with respect to which there is dissent; therefore, inclusive language resources show viewpoints that were once silenced and rejected. The analysis reveals that the words or expressions in which inclusive language resources are employed (@, x, * and -e) work as traces of harassed identities and manifest a comment by the speaker on their own enunciation. This way, this research shows that gender inclusive language holds conflict linguistic marks which point to historically denied dissidence forms, linked to gender identity and the assertion of collective rights. Finally, this article aims at, on the one hand, contributing to the description of Argentinean Spanish, and on the other, promoting reflection in favor of linguistic education at all levels, i.e. high school, undergraduate and postgraduate. Undoubtedly, opening instances of reflection and debate on the subject can have an impact on the deepening of linguistic reflection and the training of students who contribute to forging a more egalitarian society, one which is inclusive and respectful of differences.